The Association of Plasma Fractalkine and Inflammation After Ischemic Stroke - Lucia Herminawati; Andi Wijaya; Mansyur Arief; Suryani As'ad (The Prodia Education and Research Institute (PERI), 2016)
BACKGROUND: Inflammation affects the brain after stroke with main functions to rapidly eliminate the source of the disturbance, remove damaged tissue and then restore tissue homeostasis. High sensitive C-reactive protein (hsCRP) is a sensitive marker of inflammation and tissue injury in the arterial wall, while fractalkine is a distinct chemokine that promotes inflammatory signaling after neuronal death on ischemic stroke. We aim to investigate the association of fractalkine with hsCRP as a marker of inflammation in ischemic stroke patients.METHODS: This study was designed as a cross-sectional study. Soon after patients with ischemic stroke admitted to hospital, plasma fractalkine and hsCRP concentrations were assesed. Subjects had to be at least 30 years old and maximum 30 days of stroke onset. High inflammation was defined as hsCRP value >3 mg/L.RESULTS: High fractalkine levels were found on 24 ischemic stroke patients (49%) and mean of fractalkine 0.719 ng/mL on patients with stroke onset <7 days was higher than patients with stroke onset 7-30 days. Low fractalkine levels (<0.527 ng/mL) were found on ischemic stroke patients with onset 7-30 days accompanied by high inflammation (hsCRP >3 mg/L), but no significant correlation between fractalkine and hsCRP (p=0.613).CONCLUSION: High inflammation and low plasma fractalkine profile was found after 7 days of onset in ischemic stroke patients. No significant correlation between fractalkine and hsCRP in ischemic stroke patients.KEYWORDS: CRP, fractalkine, inflammation, ischemic stroke